2022
DOI: 10.3390/ijerph19116846
|View full text |Cite
|
Sign up to set email alerts
|

Association between Ultraviolet B Exposure Levels and Depression in Taiwanese Adults: A Nested Case–Control Study

Abstract: Depression is a common mental disorder that affects more than 264 million people worldwide. Anxiety, diabetes, Alzheimer’s disease, myocardial infarction, and cancer, among other disorders, are known to increase the risk of depression. Exposure to ultraviolet B (UVB) can cause human serotonin levels to increase. The vitamin D pathway is one mechanism through which ultraviolet light absorbed through the skin can affect mood; however, UVB exposure is known to increase the risk of cancer. In this study, we explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Vitamin D also modulates concentrations of gut microbiota, reducing bacterially induced activation of NF-κB in the intestine, thereby reducing remote inflammation further [153]. A nested case-control study conducted in Taiwan indicated that although moderate UVB exposure reduced risk of depression, high UVB exposure increased this risk [157]. The adjusted incidence rate ratio for moderate versus low UVB exposure was 0.89 (95% CI, 0.84-0.95); for high UVB, 1.12 (95% CI, 1.02-1.26); for very high UVB, 1.71 (95% CI, 1.51-1.95); and for extreme UVB, 2.79 (95% CI, 2.…”
Section: Major Depressive Disordermentioning
confidence: 99%
“…Vitamin D also modulates concentrations of gut microbiota, reducing bacterially induced activation of NF-κB in the intestine, thereby reducing remote inflammation further [153]. A nested case-control study conducted in Taiwan indicated that although moderate UVB exposure reduced risk of depression, high UVB exposure increased this risk [157]. The adjusted incidence rate ratio for moderate versus low UVB exposure was 0.89 (95% CI, 0.84-0.95); for high UVB, 1.12 (95% CI, 1.02-1.26); for very high UVB, 1.71 (95% CI, 1.51-1.95); and for extreme UVB, 2.79 (95% CI, 2.…”
Section: Major Depressive Disordermentioning
confidence: 99%
“…A study demonstrated that long-term exposure to moderate levels of ultraviolet B can inhibit the development of depression in Taiwan, China. 12 Besides, light therapy is effective in treating seasonal affective disorder as well as non-seasonal depression. 13 , 14 Another study also found that mental illnesses patients living in rooms with better sunlight tend to have shorter hospital stays.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, previous studies have focused on patients with mental disorders, such as depression, 12 schizophrenia 16 and have lacked exploration of the general community population. Secondly, many of these previous studies were ecological studies of the population and presented sunlight through objective meteorological data, 12 , 17 , 21 , 22 such as daytime sunshine hours and ultraviolet (UV) index.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D plays a multi-faceted role in human health. Specifically, its blood levels are associated with a range of health conditions and risks, including maternal and child health [3,4], reproductive functions [5][6][7], physical performance [8], renal function [9], and sleep quality [10], as well as diseases like cancer [11][12][13][14], lung disease [15][16][17][18][19], vascular disease [20][21][22], metabolic syndrome [23,24], dementia [25,26], psychiatric disorders [27][28][29][30], viral diseases [31][32][33][34][35] including COVID-19, and intractable diseases like myofibromyalgia [36]. Furthermore, adequate vitamin D levels can reduce chronic inflammation, a known trigger for various serious diseases [37,38].…”
Section: Introductionmentioning
confidence: 99%